Heterogeneous Security Determination System Inculcating Elgamal Cryptosystem - et. al., Angel Rubavathy B, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
ElGamal public key cryptosystem secures data using multiple output and inputs using efficient cryptosystem which provides ciphertext from plain text execution. There are many existing efficeint and modified Elgamal cryptosystem that implements different text size and data with efficient expansion time and rate. In our proposed security system heterogeneous determination of Elgamal cryptosystem inculcates various methodologies proceeding conversion of text data into binary files, arithmetic operations accomplished and it will be stored as metadata. That metadata converted into binary file and that will be stored inside the actual data. Final output will be encrypted using ElGamal algorithm using attribute based key from both encryptor side and decryptor side. Machine learning for this heterogeneous security methods will be prompted with one time three key encryption system along with fussy level selection of security implementation. Limitations assigned for file segments, user selection, key generation ranges and compacted machine learning in ElGamal algorithm endows privacy, security, robust and accuracy in data security.